Preparation of Ni3S2 and Ni3S2-Ni nanosheets via solution based processes - Busupalli, Balanagulu; Date, Kalyani S.; Datar, Suwarna; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2015)
An easy and convenient preparation of nanometer-thick sheets of Ni3S2 and Ni3S2–Ni from solution processed molecularly thin sheets of Ni-thiolates is described. Both the Ni3S2 and Ni3S2–Ni possessed sheet-like morphologies and displayed room temperature ferromagnetic characteristics. The ferromagnetic nature of these samples was also confirmed by MFM studies, and AFM/TEM investigations substantiated the sheet-like morphology of the samples.